ANALYSIS OF PUBLIC POLICY IMPLEMENTATION IN THE EMPOWERMENT OF PERSONS WITH DISABILITIES IN THE INDUSTRIAL WORLD - Yusyanah; Baby Poernomo (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Law no. 8 of 2016 concerning Persons with Disabilities, namely Article 53 paragraphs 1 and 2, stipulates that job providers from the government sector are required to employ a minimum of 2% of the number of employees with disabilities. Meanwhile, private companies are required to employ at least 1% of their employees with disabilities. Companies that do not implement this policy will be subject to sanctions. However, to date, no company or institution has ever been sanctioned for not employing people with disabilities. This is qualitative research with a phenomenological approach which aims to answer the question of how to implement government policy in Law No. 8 of 2016 regarding providing employment opportunities for people with disabilities and what efforts must be made so that this Law can be implemented effectively by stakeholders. Data collection was carried out by observing semi-structured interviews with 13 informants consisting of people with disabilities who had worked in companies, people with disabilities who had run their own MSMEs. Source triangulation was applied by interviewing company owners and human rights activists. The research results show that Law No. 8 of 2016 has not been implemented properly. This is caused not only by juridical factors, but also non-juridical factors.